Literatur Review: Analisis Faktor yang Mempengaruhi Kualitas Tidur pada Lansia - Yogi Alfianto; Aisyah Sapitri; Tyara Bella Safira; Nur Siti Aisyah; Sri Ariyanti (PPNI UNIMMAN, 2026)
Sleep quality is a crucial component of health and overall well-being among older adults, as the aging process is commonly associated with various physiological, psychological, and environmental changes that may significantly disrupt normal sleep patterns. Declining bodily functions, increased health problems, and changes in daily routines often contribute to sleep disturbances in later life. This literature review aims to analyze the factors influencing sleep quality in the elderly by synthesizing findings from relevant national and international studies published in recent years. Various factors were identified, including physiological conditions such as chronic diseases, pain, and hormonal changes; psychological factors such as anxiety, depression, stress, and cognitive decline; lifestyle-related factors such as levels of physical activity, dietary habits, medication use, and caffeine consumption; and environmental aspects including noise exposure, lighting conditions, temperature, and overall bedroom comfort. The reviewed literature consistently indicates that poor sleep quality is strongly associated with impaired physical health, reduced cognitive function, increased fatigue, and decreased emotional well-being in older adults. This review highlights the importance of comprehensive, multidisciplinary interventions that address both intrinsic and extrinsic determinants of sleep to effectively improve overall sleep quality among elderly populations.